Effect of Turmeric (Curcuma longa) Supplementation on Growth, Antioxidants and Immunity of Broilers - Sethy, Kamdev (Indian Journal of Animal Nutrition, 2021)
To assess the effect of turmeric (Curcuma longa) supplementation on growth, antioxidants and immunity of broiler chickens, one hundred twenty day-old Vencobb broiler chicks were randomly distributed into three dietary treatments with four replicates containing 10 chicks each. Group I served as control (without any supplementation), whereas birds in groups II and III were supplemented with 0.5% and 1.0% Curcuma longa powder respectively and the trial was lasted for 5 weeks. Body weight was measured at the end of each week, whereas blood samples were collected at the end of the experiment to study the antioxidant enzymes status and immunity of birds. The results indicated that addition of Curcuma longa powder caused significant (P<0.05) increase in growth and antioxidant enzymes status of birds. The cellular immune response of broiler chickens to PHA-P and antibody titre to sheep red blood cells was significantly (P<0.05) higher in treated group than un-supplemented control birds. The present results confirmed the beneficial effects of dietary Curcuma longa powder to improve growth, antioxidant enzymes and immune status of broilers.